Efektywność zamówień publicznych w świetle koncepcji kontroli zarządczej — uwagi wybrane - Małecka-Łyszczek, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In the area of public procurement, a particularly interesting research issue is a reference to the structure of management control, which requires development in the context of the forthcoming entry into force in 2021 of the new Public Procurement Law, where the principle of efficiency holds its important place. The main axis of considerations under this article will be built around an approximation of the issue of efficiency, which is a point of contact for both the concept of management control and shaping the optimal model of public procurement. At the same time, as will be indicated, effectiveness related to public procurement must be examined on a multifaceted basis, bearing in mind that its real implementation is possible by using solutions specific to the concept of management control.
Keywords: public procurement; management control; efficiency; management control standards